Lateral thoracic adipofascial flaps in the reconstruction of defects after breast-conserving surgery in breasts with ptosis mild ptosis or without ptosis - Yi Wang; Mei-li Wang; Rui Wang; Yi-bo He; Shang-nao Xie (Asian Journal of Surgery, 2023)
Objective: To study the feasibility, safety, and effectiveness of lateral thoracic adipofascial flaps in reconstructing the defects following breast-conserving surgery (BCS) in breasts with either no ptosis or mild ptosis. Methods: 37 female patients who underwent BCS and lateral thoracic adipofascial flap breast reconstruction between June 2020 and July 2022 were analysed. Surgery-related complications, intraoperative positive margin, local recurrence, and cosmetic outcome were assessed. Results: Three local complications occurred in patients, all of which were cured by conservative treatment. Additionally, four patients had intraoperative positive margins. After a median follow-up period of 17.5 months, none of the patients showed local recurrence. All patients achieved a satisfactory breast shape. Further, patients without ptosis achieved good volume and symmetry. However, the breast symmetry was not satisfactory for patients with ptosis. Conclusion: It is reliable and effective to use the lateral thoracic adipofascial flaps to reconstruct the defects after BCS when the breast is not ptotic and the lesions are located in the lateral and central quadrants.